Construction of Chiral Tri‐ and Tetra‐Arylmethanes Bearing Quaternary Carbon Centers: Copper‐Catalyzed Enantioselective Propargylation of Indoles with Propargylic Esters. (27th June 2016) - Tsuchida, Kouhei; Senda, Yasushi; Nakajima, Kazunari; Nishibayashi, Yoshiaki
Abstract: Copper‐catalyzed enantioselective propargylation of indoles with propargylic esters and sequential Huisgen cycloaddition with azides lead to the construction of chiral triarylmethanes, bearing a quaternary carbon center, with high to excellent enantioselectivities. The result described herein can be used in the enantioselective preparation of a tetraarylmethane.